Pseudo-nitzschia sp. diversity and seasonality in the southern North Sea, domoic acid levels and associated phytoplankton communities. (15th December 2018) - Delegrange, A.; Lefebvre, A.; Gohin, F.; Courcot, L.; Vincent, D.
Abstract: The diversity, toxicity and seasonality of Pseudo-nitzschia sp. were investigated from February to November 2012 in the southern Bight of the North Sea (SBNS) along the French coast. The identification of Pseudo-nitzschia species in this area was addressed for the first time in this study. Our results revealed a low species richness (3 distinct species) in association with moderate (102 pg mL −1 ) to high (263 pg mL −1 ) domoic acid (DA) levels in autumn and spring, respectively. Pseudo-nitzschia succession corresponded to the dominance of P. delicatissima in April–May (86% of total diatoms) as a co-occurring species of the Phaeocystis globosa bloom. Following the Phaeocystis bloom (May–September), P. pungens dominated markedly over P. fraudulenta and P. delicatissima and was the only species present in autumn, although at low abundance (<1000 cell L −1 ). The results of this study support the idea that Pseudo-nitzschia seasonality in the SBNS relies principally on temperature and nutrient availability (DIN and silicates), which, in turn, depend on locally fluctuating environmental conditions (rainfalls and winds). This study highlights the potential for the SBNS to be a potential risk area in regard to the possible impacts of DA on marine resources and the DA transfer through marine food webs. This is of particular concern since DA concentration in seawater was not systematically correlated to potentially toxic Pseudo-nitzschia abundance. Highlights: Low Pseudo-nitzschia sp. diversity (three species) in the southern North Sea. Domoic acid levels reached 263 pg mL −1 in May 2012, 83% as dissolved DA. Strong species seasonality driven by temperature and nutrient availability (DIN and silicates). Autumnal DA concentrations could be attributed to P. pungens. DA concentration was not systematically correlated to Pseudo-nitzschia spp. abundance.